Modified polyphenylene sulfide fiber, fiber fabric thereof, preparation method and use thereof

By using linear polyphenylene sulfide, amorphous reactive polymer containing oxazoline groups and hydrophilic inorganic nanoparticles, modified polyphenylene sulfide fibers, the poor hydrophilic aging and sulfonation processing of alkaline electrolytic hydrogen separators have been solved, and the membrane with high mechanical strength and long-term hydrophilic properties is achieved.

CN119571500BActive Publication Date: 2025-04-15ZHEJIANG JULING NEW MATERIALS CO LTD +2
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510112147.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-15
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing alkaline electrolytic hydrogen-producing membranes have poor hydrophilic aging, and the sulfonation processing requires the use of a large amount of strong acids, which affects the environment and product safety.

Method used

Linear polyphenylene sulfide, amorphous reactive polymer containing oxazoline groups and hydrophilic inorganic nanoparticles are prepared by mixing and double screw extrusion mechanism, and a single screw extruder is spinned into modified polyphenylene sulfide fibers, which are used to prepare alkaline electrolytic water hydrogen production separators.

Benefits of technology

It improves the hydrophilicity and mechanical strength of the modified polyphenylene sulfide fibers, extends the service life of the membrane, and avoids the negative impact of sulfonation processing on the environment and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of alkaline water electrolysis hydrogen production diaphragm, and specifically to a modified polyphenylene sulfide fiber, its fiber fabric, preparation method and use. The modified polyphenylene sulfide fiber uses hydrophilic inorganic nanoparticles and amorphous reactive polymers containing oxazoline groups to modify linear polyphenylene sulfide. The polyphenylene sulfide fabric woven from the obtained modified polyphenylene sulfide fiber has good hydrophilicity, and the diaphragm made of water electrolysis hydrogen production has good conductivity and gas isolation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alkaline water electrolysis hydrogen production diaphragm, and in particular to a modified polyphenylene sulfide fiber, its fiber fabric, and a preparation method and application thereof. Background Art

[0002] The diaphragm is the main core material of alkaline water electrolysis hydrogen production equipment. It is placed between the anode and cathode of the water electrolyzer to prevent the mixing of oxygen and hydrogen. It should have certain mechanical strength, corrosion resistance and charge permeability to ensure gas purity, improve current efficiency and safety. Therefore, the water electrolysis hydrogen production diaphragm must have high density and good hydrophilicity.

[0003] Polyphenylene Sulfide (PPS) is a linear or branched polymer without a crystalline melting point. It is composed of benzene rings and sulfur atoms connected alternately, and the structural unit is a phenylene sulfide group. As early as the 1970s, industrial production has been realized. With the improvement of synthesis technology, the performance of PPS has been continuously improved, especially the successful development of linear PPS, which has made the industrial production of PPS fiber a reality. PPS fiber has the following characteristics: good thermal stability, can work at a high temperature of 190°C for a long time; good flame retardancy, the limiting oxygen index is greater than 31, it does not burn under normal circumstances, and the amount of smoke is low when burning; good chemical resistance, insoluble in any solvent below 200°C; good creep and electrical properties. Therefore, it has been used in alkaline hydrogen production diaphragms.

[0004] In order to make the electrolytic water hydrogen production membrane fabric have long-term hydrophilic durability and excellent ion permeability, Chinese patent CN104746202A discloses a high-density woven fabric supported by PPS fibers, and the woven fabric is subjected to vacuum plasma surface treatment to obtain a PPS water electrolyzer diaphragm. However, since the plasma processing only treats the fiber surface, the hydrophilic timeliness of the hydrogen diaphragm is poor. As the diaphragm is used for a longer time, the hydrophilicity and airtightness of the diaphragm will gradually decrease, thereby affecting the production efficiency. Chinese patent documents CN101372752A and CN113201839A disclose a nonwoven fabric and a staple fabric made of PPS fiber, and the woven fabric is sulfonated to obtain a PPS water electrolyzer diaphragm. However, due to the low strength of the nonwoven fabric and the staple fabric, the service life will be affected in actual use, thereby affecting the production efficiency. In addition, the sulfonation process is to treat the polyphenylene sulfide fabric with high-temperature strong acid, which requires the use of a large amount of strong acid, which not only affects the environment, but also has an adverse effect on the safety of the product. Hydrophilic inorganic nanoparticles are also used for the modification of PPS and the preparation of water electrolysis hydrogen production diaphragms, such as the water electrolysis hydrogen production diaphragms disclosed in CN117286538A and CN003862821A. However, it requires the use of auxiliary agents such as polyvinyl pyrrolidone, and the diaphragm strength is relatively low. Summary of the invention

[0005] In order to solve the deficiencies of the prior art, the purpose of the present invention is to provide a modified polyphenylene sulfide fiber, its fiber fabric, preparation method and use. To achieve the above purpose, the technical solution of the present invention is as follows:

[0006] First, the present invention provides a modified polyphenylene sulfide fiber. The modified polyphenylene sulfide fiber is made of linear polyphenylene sulfide, an amorphous reactive polymer containing oxazoline groups and hydrophilic inorganic nanoparticles through mixing, preparing blended particles with a twin-screw extruder, extruding with a single-screw extruder, and spinning. During the mixing, the weight ratio of the linear polyphenylene sulfide, the amorphous reactive polymer containing oxazoline groups and the hydrophilic inorganic nanoparticles used in the modified polyphenylene sulfide fiber is (49-60):(0.1-50):(0.1-40), that is, the weight percentage of the linear polyphenylene sulfide is 49%-60%, the weight percentage of the amorphous reactive polymer containing oxazoline groups is 0.1%-50%, and the weight percentage of the hydrophilic inorganic nanoparticles is 0.1%-40%.

[0007] Preferably, the particle size of the hydrophilic inorganic nanoparticles is 10 nm to 50 nm.

[0008] Preferably, the hydrophilic inorganic nanoparticles are selected from one or more of zirconium oxide, silicon oxide, aluminum oxide and zinc oxide.

[0009] Preferably, the amorphous reactive polymer containing oxazoline groups is one or both of a polymer of 4,5-dihydro-2-(1-methylvinyl)-oxazole and vinylbenzene (CAS No.: 30174-74-4) and a polymer of 4,5-dihydro-2-(1-methylvinyl)-oxazole and acrylonitrile-based styrene (CAS No.: 100920-92-1).

[0010] Preferably, the molecular weight dispersion index Mw / Mn of the linear polyphenylene sulfide is ≤5.

[0011] Preferably, the linear polyphenylene sulfide has a melt index of 10 g / 10 min to 400 g / 10 min.

[0012] Preferably, the weight average molecular weight of the linear polyphenylene sulfide is 25,000 to 65,000.

[0013] Preferably, the phenylene sulfide unit content of the linear polyphenylene sulfide is ≥90% (mol / mol).

[0014] Second, a method for preparing the aforementioned modified polyphenylene sulfide fiber comprises the following steps:

[0015] S1: Take linear polyphenylene sulfide raw material, amorphous reactive polymer containing oxazoline group and hydrophilic inorganic nanoparticles and mix them to obtain fiber raw material blend, and extrude the fiber raw material blend through a twin-screw extruder. The feeding port of the twin-screw extruder is protected by nitrogen; the twin-screw extruder is divided into 12 sections for heating control, the feeding port of zone 1 is water-cooled at 20℃~60℃; zones 2 to 5 are 280℃~310℃; zones 6 to 9 are 290℃~325℃; zones 10 to 12 are 280℃~300℃; the material is extruded from the die, and the die temperature is 300℃~325℃; then it is cooled and pelletized to obtain fiber raw material blend particles;

[0016] S2: Dry the fiber raw material blended pellets in a vacuum dryer at 140°C and 0.063MPa pressure for 8h. Input the dried fiber raw material blended pellets into a single screw extruder, and the feed port of the single screw extruder is protected by nitrogen; the single screw extruder is heated and controlled in 5 sections, the heating temperature of the first section is 230°C~280°C, the heating temperature of the second section is 280°C~330°C, the heating temperature of the third section is 290°C~340°C, the heating temperature of the fourth section is 300°C~350°C, and the heating temperature of the fifth section is 290°C~340°C. The blend is conveyed to the spinning assembly through a single screw extruder, and is spun into spun yarn through the spinning assembly. The spun yarn is stretched, shaped and wound to obtain polyphenylene sulfide fiber; the spinning method is: melt spinning at 310°C, the raw yarn is cooled at 20°C, the stretching temperature is 110°C, the stretching ratio is 4.5 times, the shaping temperature is 250°C, and the winding is carried out at 2500m / min.

[0017] Third: A polyphenylene sulfide fabric, made of the aforementioned modified polyphenylene sulfide fiber, the preparation method of the polyphenylene sulfide fabric comprising the following steps:

[0018] S3: The modified polyphenylene sulfide fibers are twisted into yarns with a fineness of 1800 dtex and a twist coefficient of 320, which are used as warp yarns and weft yarns to prepare plain fabrics with a warp density of 10 to 50 yarns / cm and a weft density of 8 to 40 yarns / cm; the plain fabrics are refined at a temperature of 80°C to 100°C and a speed of 5 m / min to 50 m / min, and then dried with a cylinder dryer at 80°C to 150°C to prepare polyphenylene sulfide fabrics for hydrogen production membranes using electrolysis of water with a thickness of 0.1 to 3.0 mm.

[0019] Preferably, the single fiber density of the modified polyphenylene sulfide fiber before plying is 0.3 dtex to 30 dtex.

[0020] Fourth: Use of the aforementioned modified polyphenylene sulfide fiber or the aforementioned polyphenylene sulfide fabric in preparing a diaphragm for producing hydrogen by alkaline water electrolysis.

[0021] Fifth: A diaphragm for producing hydrogen by alkaline water electrolysis, comprising the aforementioned modified polyphenylene sulfide fiber or the aforementioned polyphenylene sulfide.

[0022] The present invention has the following beneficial effects:

[0023] The present invention uses hydrophilic inorganic nanoparticles and amorphous reactive polymers containing oxazoline groups to improve the hydrophilicity of modified polyphenylene sulfide fibers, and the amorphous reactive polymers containing oxazoline groups can be used as chain extenders for linear polyphenylene sulfide, while playing the role of aqueous inorganic nanoparticle compatibilizers and dispersing aids, and further improving the hydrophilicity of polyphenylene sulfide fibers. Tests have shown that the modified polyphenylene sulfide fibers not only have high mechanical strength, but also have excellent and long-lasting hydrophilic properties in the use of hydrogen production membranes.

[0024] The modified polyphenylene sulfide fiber prepared according to the present invention, even if the polyphenylene sulfide fiber fabric is not subjected to subsequent sulfonation treatment, plasma treatment or even ultraviolet treatment, by adding hydrophilic inorganic nanoparticles and amorphous reactive polymers containing oxazoline groups (the amorphous reactive polymers containing oxazoline groups serve as chain extenders for polyphenylene sulfide polymers, and the generated amide bonds have certain hydrophilicity), the obtained modified polyphenylene sulfide fiber not only has high mechanical strength, but also has excellent properties as a diaphragm cloth for diaphragms for hydrogen production by electrolysis of water, including alkali resistance, low resistance and gas isolation capability. DETAILED DESCRIPTION

[0025] In order to clearly demonstrate the purpose, technical solutions and advantages of the present invention, the present invention is further described below in conjunction with embodiments. The specific embodiments described in this section are only used to explain the present invention and are not used to limit the scope of protection of the present invention.

[0026] In the following examples, the polyphenylene sulfide raw material (linear polyphenylene sulfide) is a commercially available product (Zhejiang Xinhecheng Special Materials Co., Ltd.; Shandong Invite New Materials Co., Ltd.), the product weight average molecular weight is 25000-65000, the phenylene sulfide unit ( , i.e. -C6H 4- The S-unit) content is ≥90% (mol / mol); the amorphous reactive polymer containing oxazoline groups is a commercially available product (Nippon Shokubai Co., Ltd.).

[0027] In the following examples, the modified polyphenylene sulfide fibers are prepared into modified polyphenylene sulfide fiber filaments for preparing polyphenylene sulfide fabrics. However, it is well known to those skilled in the art that polyphenylene sulfide fiber staples can also be used to prepare polyphenylene sulfide fabrics and diaphragm materials for alkaline water electrolysis to produce hydrogen.

[0028] Example 1 Preparation of modified polyphenylene sulfide fiber and modified polyphenylene sulfide fabric

[0029] The raw materials and other information of the modified polyphenylene sulfide fiber are shown in Table 1. Preparation method of modified polyphenylene sulfide fiber and modified polyphenylene sulfide fabric:

[0030] 1) Linear polyphenylene sulfide raw material, amorphous reactive polymer containing oxazoline group (polymer of 4,5-dihydro-2-(1-methylvinyl)-oxazole and vinylbenzene; CAS number: 30174-74-4) and zirconium oxide nanoparticles are mixed in a weight ratio of 60:30:10 to obtain a fiber raw material blend, and the fiber raw material blend is mixed and extruded through a twin-screw extruder. The feed port of the twin-screw extruder is protected by nitrogen to prevent the material from high-temperature oxidation; the twin-screw extruder is divided into 12 sections for heating control, the feed port of zone 1 is water-cooled at 20℃~60℃; zone 2 to zone 5 is 280℃~310℃; zone 6 to zone 9 is 290℃~325℃; zone 10 to zone 12 is 280℃~300℃; the material is extruded from the die, and the die temperature is 300℃~325℃; then it is cooled and pelletized to obtain fiber raw material blend pellets.

[0031] 2) Dry the fiber raw material blended pellets in a vacuum dryer at 140°C and 0.063MPa pressure for 8h. Input the dried fiber raw material blended pellets into a single screw extruder. The feed port of the single screw extruder is protected by nitrogen to prevent the material from high temperature oxidation. The single screw extruder is heated and controlled in 5 sections. The heating temperature of the first section is 230°C~280°C, the heating temperature of the second section is 280°C~330°C, the heating temperature of the third section is 290°C~340°C, the heating temperature of the fourth section is 300°C~350°C, and the heating temperature of the fifth section is 290°C~340°C. The blended material is transported to the spinning assembly through the single screw extruder, and the spinning assembly is spun into spun yarn. The spun yarn is stretched, shaped and wound to obtain modified polyphenylene sulfide fiber. The physical properties of the modified polyphenylene sulfide fiber are shown in Table 1.

[0032] The spinning method is as follows: melt spinning at 310°C, cooling the raw silk at 20°C, drawing temperature at 110°C, drawing ratio at 4.5 times, setting temperature at 250°C, and winding at 2500m / min.

[0033] 3) The modified polyphenylene sulfide fibers prepared in step 2) with a single fiber density of 10 dtex and a twist coefficient of 310 are plied together to form polyphenylene sulfide yarns with a fineness of 1800 dtex and a twist coefficient of 320. The plied polyphenylene sulfide yarns are used as warp yarns and weft yarns, and are woven on a rapier loom to prepare a plain fabric with a warp density of 16 yarns / cm and a weft density of 11 yarns / cm. The obtained plain fabric is refined at a temperature of 90°C and a speed of 25 m / min, and then dried at 135°C using a cylinder dryer to prepare a polyphenylene sulfide fabric for a hydrogen production membrane for electrolysis of water with a thickness of 0.9 mm.

[0034] The formula parameters and performance parameters of the polyphenylene sulfide fabric are shown in Table 1.

[0035] Example 2 Preparation of modified polyphenylene sulfide fiber and modified polyphenylene sulfide fabric

[0036] See Example 1 and Table 1.

[0037] The modified polyphenylene sulfide fiber uses an amorphous reactive polymer containing oxazoline groups, which is a polymer of 4,5-dihydro-2-(1-methylvinyl)-oxazole and acrylonitrile-based styrene (CAS No.: 100920-92-1). The weight ratio of the linear polyphenylene sulfide raw material, the amorphous reactive polymer containing oxazoline groups, and the hydrophilic inorganic nanoparticles is 59.9:0.1:40.

[0038] In step 3), the single filament density is 0.3 dtex, the warp density is 50 yarns / cm, and the weft density is 40 yarns / cm. The plain fabric is refined at a temperature of 100°C and a speed of 50 m / min, and then dried with a cylinder dryer at 150°C to prepare a polyphenylene sulfide fabric for electrolysis of water hydrogen production diaphragm with a thickness of 3.0 mm. The formula parameters and performance parameters of the polyphenylene sulfide fabric are shown in Table 1. Other preparation methods and process parameters are the same as those in Example 1.

[0039] Example 3 Preparation of modified polyphenylene sulfide fiber and modified polyphenylene sulfide fabric

[0040] See Example 1 and Table 1.

[0041] The amorphous reactive polymer containing oxazoline groups used in the modified polyphenylene sulfide fiber is a polymer of 4,5-dihydro-2-(1-methylvinyl)-oxazole and vinylbenzene (CAS No.: 30174-74-4). The weight ratio of the linear polyphenylene sulfide raw material, the amorphous reactive polymer containing oxazoline groups and the hydrophilic inorganic nanoparticles is 49.9:50:0.1.

[0042] In step 3), the single fiber density is 30 dtex, the warp density is 10 yarns / cm, and the weft density is 8 yarns / cm. The plain fabric is refined at a temperature of 80°C and a speed of 5 m / min, and then dried with a cylinder dryer at 80°C to prepare a polyphenylene sulfide fabric for electrolysis hydrogen production membrane with a thickness of 0.1 mm.

[0043] The formulation parameters and performance parameters of the polyphenylene sulfide fabric are shown in Table 1. Other preparation methods and process parameters are the same as those in Example 1.

[0044] Comparative Example 1 Preparation of modified polyphenylene sulfide fiber and modified polyphenylene sulfide fabric

[0045] As in Example 1, the difference is that: in step 1), no amorphous reactive polymer containing oxazoline groups is added (ie, the weight ratio of linear polyphenylene sulfide raw material to hydrophilic inorganic nanoparticles is 90:10). Other preparation parameters and performance parameters of the polyphenylene sulfide fabric are shown in Table 1.

[0046] Comparative Example 2 Preparation of modified polyphenylene sulfide fiber and modified polyphenylene sulfide fabric

[0047] As in Example 1, the difference is that in step 1), the weight ratio of the linear polyphenylene sulfide raw material, the amorphous reactive polymer containing oxazoline groups, and the hydrophilic inorganic nanoparticles is 35:55:10. Other preparation parameters and performance parameters of the polyphenylene sulfide fabric are shown in Table 1.

[0048] Product testing or calculation method:

[0049] (1) Melt index value measurement: According to JIS K7210 (revised in 1999), at a temperature of 315.5°C and a load

[0050] The melt index value was measured at 5000 g.

[0051] (2) Total fineness: Based on JIS L1013 (1999) 8.3.1.A method, with a load of 0.045 cN / dtex

[0052] To determine the positive fineness, as the total fineness.

[0053] (3) Number of single filaments: calculated according to the method of JIS L1013 (1999) 8.4.

[0054] (4) Calculation of single yarn fineness: Calculated by dividing the above total fineness by the above number of single yarns.

[0055] Strength and elongation test: According to the constant speed elongation test shown in JIS L1013 (1999) 8.5.1 standard

[0056] The test was conducted under the conditions of a gripping interval of 250 mm and a tensile speed of 300 mm / min. The elongation was calculated from the elongation at the point of maximum force in the SS curve.

[0057] (5) Water absorption rate test: The test was conducted according to the dropping method in 7.1.1 of JIS L1907-2010 Test method for water absorption of fiber products. A certain amount of deionized water was added to the burette, and the burette was fixed vertically. The diaphragm cloth to be tested was flattened with a hoop and placed horizontally under the burette. The position of the burette was adjusted so that the bottom of the burette was 1 cm away from the cloth surface. The piston of the burette was slowly opened to ensure that the amount of water dripped onto the cloth surface was one drop. The time it took for the water drop to be completely absorbed was recorded with a stopwatch. Each group of samples was tested at least 5 times and the average value was taken.

[0058] (6) Water absorption height detection: The test is conducted according to 7.1.2 climbing method in JIS L1907-2010 Test method for water absorption of fiber products. The sample size is 30 cm × 2.5 cm. The sample is clamped vertically on the test clamp. A certain amount of deionized water is added to the water injection container below so that the lower 2 cm of the sample is immersed in water. The water is kept for 10 minutes. A mark is made at the highest point of water absorption of the sample. The sample is removed from the sample clamp and the water absorption height is measured horizontally. Each group of samples is measured at least 3 times and the average value is taken.

[0059] (7) Long-term heat and alkali resistance test: The tensile strength of the fabric was tested using the method of GB / T3923.1-2013 "Tensile properties of textile fabrics - Part 1: Determination of breaking strength and elongation at break (strip method)". The fabric was then placed in a 30wt% KOH solution and heated to 80°C for 300 h. The tensile strength of the fabric was then tested again using the method of GB / T3923.1-2013 "Tensile properties of textile fabrics - Part 1: Determination of breaking strength and elongation at break (strip method)". The breaking strength retention rate was calculated by the fabric strength after hot alkali treatment / fabric strength before hot alkali treatment * 100%. After hot alkali treatment, the fabric strength will decrease. If the fabric has a high strength retention rate after hot alkali treatment, it indicates that the fabric has good long-term heat and alkali resistance.

[0060] (8) Detection of oxygen content in hydrogen: Use an explosion-proof online hydrogen oxygen analyzer to detect the trace oxygen content at the negative electrode outlet of the water electrolyzer. According to the requirements for hydrogen and oxygen content in hydrogen in GBT 3634.1-2006 Hydrogen Part 1 Industrial Hydrogen, the following classification is made:

[0061] Qualified products: Hydrogen (H2) volume fraction ≥ 99.00%; oxygen (O2) volume fraction ≤ 0.40%

[0062] First-class products: Hydrogen (H2) volume fraction ≥ 99.50%; oxygen (O2) volume fraction ≤ 0.20%

[0063] Superior products: The volume fraction of hydrogen (H2) is ≥99.95%; the volume fraction of oxygen (O2) is ≤0.01%.

[0064] (9) Surface resistance detection: Use the method of "SJT 10171.5-1991 Determination of diaphragm surface resistance" to measure the resistance value R2 of the 40mm*60mm diaphragm immersed in 40% potassium hydroxide solution, and the resistance value R1 of the potassium hydroxide solution of the same concentration. The product of the difference between R1 and R2 and the diaphragm area is the resistance R of the diaphragm, expressed in Ω*cm 2 express.

[0065] The diaphragm resistance R is calculated using the formula: R = (R2-R1) * S; where: R is the surface resistance of the sample, Ω*cm 2 ; R1 is the resistance value of the solution, Ω; R2 is the total resistance value of the sample and the solution, Ω; S is the test area of ​​the diaphragm, cm 2 .

[0066] Table 1 Ingredients, preparation and performance parameters of different test samples

[0067]

[0068] As can be seen from Table 1, the gas insulation capacity of the polyphenylene sulfide fabric of Comparative Example 1 does not meet the requirements and the surface resistance is large; the polyphenylene sulfide fabric of Comparative Example 2 has poor alkali resistance, poor fiber strength and low elongation at break. The polyphenylene sulfide fabrics of Examples 1 to 3 have good fiber strength, water climbing height, gas insulation capacity, surface resistance and other properties.

Claims

1. A modified polyphenylene sulfide fiber, characterized in that: The modified polyphenylene sulfide fiber is made of linear polyphenylene sulfide, amorphous reactive polymer containing oxazoline groups and hydrophilic inorganic nanoparticles through mixing, preparing blended particles by a twin-screw extruder, extruding by a single-screw extruder, and spinning. During the mixing, the weight ratio of the linear polyphenylene sulfide, the amorphous reactive polymer containing oxazoline groups and the hydrophilic inorganic nanoparticles used in the modified polyphenylene sulfide fiber is (49-60): (0.1-50): (0.1-40); the amorphous reactive polymer containing oxazoline groups is at least one of a polymer of 4,5-dihydro-2-(1-methylvinyl)-oxazole and vinylbenzene, and a polymer of 4,5-dihydro-2-(1-methylvinyl)-oxazole and acrylonitrile-based styrene; and the hydrophilic inorganic nanoparticles are selected from one or more of zirconium oxide, silicon oxide, aluminum oxide, and zinc oxide.

2. The modified polyphenylene sulfide fiber according to claim 1, characterized in that: The particle size of the hydrophilic inorganic nanoparticles is 10 nm to 50 nm.

3. The modified polyphenylene sulfide fiber according to claim 1, characterized in that: The molecular weight dispersion index Mw / Mn of the linear polyphenylene sulfide is ≤5.

4. The modified polyphenylene sulfide fiber according to claim 1, characterized in that: The linear polyphenylene sulfide has a melt index of 10 g / 10 min to 400 g / 10 min.

5. A method for preparing a modified polyphenylene sulfide fiber according to any one of claims 1 to 4, comprising the following steps: S1: taking a linear polyphenylene sulfide raw material, an amorphous reactive polymer containing an oxazoline group and a hydrophilic inorganic nanoparticle and mixing them to obtain a fiber raw material blend, and mixing and extruding the fiber raw material blend through a twin-screw extruder; the feeding port of the twin-screw extruder is protected by nitrogen; the twin-screw extruder is divided into 12 sections for heating control, the feeding port of zone 1 is water-cooled at 20°C~60°C; zones 2 to 5 are 280°C~310°C; zones 6 to 9 are 290°C~325°C; zones 10 to 12 are 280°C~300°C; the material is extruded from a die, and the die temperature is 300°C~325°C; and then cooled and pelletized to obtain fiber raw material blend pellets; S2: Dry the fiber raw material blended pellets in a vacuum dryer at 140°C and 0.063MPa pressure for 8h; input the dried fiber raw material blended pellets into a single screw extruder, and the feed port of the single screw extruder is protected by nitrogen; the single screw extruder is heated and controlled in 5 sections, the first section heating temperature is 230°C~280°C, the second section heating temperature is 280°C~330°C, the third section heating temperature is 290°C~340°C, and the fourth section heating temperature is 240°C~350°C. The temperature of the fifth stage is 300℃~350℃, and the heating temperature of the fifth stage is 290℃~340℃; the blend is transported to the spinning assembly through a single screw extruder, and spun into spun yarn through the spinning assembly, and the spun yarn is stretched, shaped and wound to obtain polyphenylene sulfide fiber; the spinning method is: melt spinning at 310℃, the raw yarn is cooled at 20℃, the stretching temperature is 110℃, the stretching ratio is 4.5 times, the shaping temperature is 250℃, and the winding is carried out at 2500m / min.

6. A polyphenylene sulfide fabric, characterized in that: The modified polyphenylene sulfide fiber is made by the method for preparing a modified polyphenylene sulfide fiber according to claim 5, and the preparation method of the polyphenylene sulfide fabric comprises the following steps: S3: The modified polyphenylene sulfide fibers are twisted into yarns with a fineness of 1800 dtex and a twist coefficient of 320, which are used as warp yarns and weft yarns to prepare plain fabrics with a warp density of 10 to 50 yarns / cm and a weft density of 8 to 40 yarns / cm; the plain fabrics are refined at a temperature of 80°C to 100°C and a speed of 5 m / min to 50 m / min, and then dried with a cylinder dryer at 80°C to 150°C to prepare polyphenylene sulfide fabrics for hydrogen production membranes using electrolysis of water with a thickness of 0.1 to 3.0 mm.

7. The polyphenylene sulfide fabric according to claim 6, characterized in that: The single fiber density of the modified polyphenylene sulfide fiber before plying is 0.3 dtex to 30 dtex.

8. Use of the modified polyphenylene sulfide fiber according to any one of claims 1 to 4 or the polyphenylene sulfide fabric according to claim 6 in preparing a diaphragm for hydrogen production by alkaline water electrolysis.

9. A diaphragm for producing hydrogen by alkaline water electrolysis, characterized in that: Containing the modified polyphenylene sulfide fiber according to any one of claims 1 to 4 or the polyphenylene sulfide fabric according to claim 6.

Citation Information

Patent Citations

  • High temperature resistant alkaline water electrolytic cell barrier diaphragm and preparation thereof

    CN101372752A

  • Diaphragm cloth for water electrolyser and producing method thereof

    CN104746202A

  • Polyphenylene sulfide fabric for water electrolyser as well as preparation method and application of polyphenylene sulfide fabric

    CN113201839A

  • High-temperature-resistant and wide-temperature-range applicable alkaline water electrolysis hydrogen production composite diaphragm as well as preparation method and application thereof

    CN117286538A

  • High-strength polyphenylene sulfide / polyethylene terephthalate blend resin composition and its preparation method

    CN102272230A